The OSHA formaldehyde standard - Sanger, John M.; The MARCOM Group, Ltd. ([Boothwyn, PA] : The MARCOM Group, Ltd., 1993)
This program explains on health hazards associated with formaldehyde, testing for permissible exposure limits (PEL) and short term exposure limits (STEL), labeling and material safety data sheets, hoods and pther ventilating systems, using personal protective equipment, spill cleanup and decontamination procedures, first aid for formaldehyde-related procedures and medical surveillance plans
Title from title screen
Executive producer, Donald L. Leonard
Keywords: Formaldehyde -- Standards; Formaldehyde -- Safety measures